Academic Reading: Using SQ3R Method to Improve Students' Reading Skill - Rohmah, Azka Alimatur; Wahyuningsih, Sri (LINGUAMEDIA Journal, 2023)
Reading is an active process that involves a person focusing on the reading text. It helps students improve their critical thinking skills and reading skills. The ability to read is needed in student learning today. By reading, students get a lot of information. Not only to retrieve information but also to learn grammar, vocabulary, and pronunciation. Therefore, a method is needed to improve students’ reading skills, some of which are often used, such as the SQ3R method and critical reading. This study aims to determine the role of the SQ3R method and critical reading in improving students' reading skills. This study uses a qualitative method in the form of interviews conducted virtually through a communication application (WhatsApp) with students at an Indonesian higher education. The results of this study show that the SQ3R reading method is helpful for students in improving their reading skills and critical thinking.